Comparison of different cultures and culturing conditions for the biological deterioration of organic load from real saline bilge wastewater: microbial diversity insights and ecotoxicity assessment - Mazioti, Aikaterini A; Vasquez Christodoulou, Marlen; Vyrides, Ioannis (My University, 2021)
Bilge wastewater is a high strength, typically saline wastewater, originating from operation of ships. In this study, the treatment of real bilge wastewater was tested using pure isolated aerobic strains and mixed cultures (aerobic and anaerobic). The Chemical Oxygen Demand (COD) and ecotoxicity decrease were monitored over time, while the microbial dynamics alterations in mixed cultures were also recorded. The isolated strains Pseudodonghicola xiamenensis, Halomonas alkaliphila and Vibrio antiquaries were shown to significantly biodegrade bilge wastewater. Reasonable COD removal rates were achieved by aerobic mixed cultures (59%, 9 days), while anaerobic mixed cultures showed lower performance (34%, 51 days). The genus Pseudodonghicola was identified as dominant under aerobic conditions both in the mixed cultures and in the control sample (raw wastewater), after exposure to bilge wastewater, demonstrating natural proliferation of the genus and potential contribution to COD reduction. Biodegradation rates were higher when initial organic load was high, while the toxicity of raw wastewater partially decreased after treatment.
Keywords: Aerobic treatment; Anaerobic granular sludge; Mixed bacterial cultures; Oily wastewater; Pseudodonghicola xiamenensis; Pure strains